SCREEN ARTS VIEWED BY THE VILLAGE AT THE BEGINNING OF THE 20TH AND 21ST CENTURIES: ON REMEDIATION OF COMMENTATOR FIGURE / СЕЛО У ЭКРАНА В НАЧАЛЕ XX И XXI ВЕКОВ: ОЧЕРК О РЕМЕДИАЦИИ ФИГУРЫ КОММЕНТАТОРА - KHAIRUTDINOVA ALINA A. / ХАЙРУТДИНОВА А.А.; CHUMAKOVA VARVARA P. / ЧУМАКОВА В.П. (Наука телевидения)
In the article, the authors make an attempt to compare the processes of media consumption and media use in the Russian countryside in the early 20th and early 21st centuries, in particular the problems of the rural people learning the new language of screen arts. Today, the media consumption of the Russian village is not actively explored, so empirical material based on five expeditions to the Russian countryside in the period from 2012 to 2018 is of particular importance. The materials on the 20th century are archival documents and testimonies of the participants in the cinema of the village. Based on the difference between oral and written cultures, the authors show that, both in the beginning of the 20th and both in the beginning of the 21st century the villagers lack media literacy to perceive the diversity of the language of screen arts. And it is compensated by the figure of the commentator. But if at the beginning of the 20th century the commentator is located next to the cine-camera, then in the 21st century it is already placed inside the screen. The article suggests that a modern TV presenter, placed inside the screen, is a remediation of the commentator who conducted explanatory work among villagers in the early 20th century in the Soviet cinema process. At the same time, the commentator’s figure keeps the Russian village from forming a polymedia environment, since the choice of content is still limited by insufficient media literacy.